Pengaruh Hubungan Sosial Terhadap Produktivitas Kerja unit PKP-PK - Anas Masruri; Dimas Dwi Oktafino; Hilman Munawwar A; Muhammad Dima Alfiansyah; Oke Hendra (Politeknik Penerbangan Indonesia Curug, 2021)
This research made to determine how the influence of social relations factors on the productivity level of the performance of ARFF officers at the airport. The method used in making this journal is a qualitative method. The data were obtained from the author's observations during On the Job Training (OJT) activities at the relevant airports as well as from the results of distributing questionnaires to ARFF personnel targets. From the results of the study it can be concluded that the social relationship factor is an influential factor on the work productivity of the PKP-PK unit. And by establishing good communication within the organization is a way to maintain good social relations in the work environment.